Metagenomic and physicochemical analyses reveal microbial community and functional differences between three types of low-temperature Daqu. (June 2022) - Hou, Qiangchuan; Wang, Yurong; Cai, Wenchao; Ni, Hui; Zhao, Huijun; Zhang, Zhendong; Liu, Zhongjun; Liu, Jiming; Zhong, Ji'an; Guo, Zhuang
Graphical abstract: Highlights: The abundance ratio of bacteria to fungi in low-temperature Daqu was above 4:1. Temperature mainly affects the microbial abundance in low-temperature Daqu. Microbes in Qingcha and Hongxin have strong ability to degrade macromolecules. Microbes in Houhuo have strong ability to produce flavor substances in liquor. Microbial functions of different types of low-temperature Daqu were complementary. Abstract: Complex microbes of different types of low-temperature Daqu (LTD) play an important role in the formation of flavors and qualities of light-flavor Baijiu during fermentation. However, characterizing the taxonomic and functional diversity of microbiota in three types of LTD (Houhuo, Hongxin, Qingcha) remains a major challenge. The present study combined metagenomic sequencing with culture-based methods and physicochemical analysis to compare the three LTD microbiota and elucidate their function in LFB brewing. The results revealed a high diversity of microbes in LTD, with 1286 genera and 4157 species detected across all studied samples. Bacteria and fungi were the main microbes in LTD, with a bacterial to fungal relative abundance ratio of above 4:1. Bacillus (21.18%) and Bacillus licheniformis (17.45%) were the most abundant microbes in the LTD microbiota at the genus and species levels, respectively. Culture-dependent analysis found the highest abundances of bacteria, fungi, and lactic acid bacteria in Houhuo, while the metagenomic-based microbiota found that the relative abundance of bacteria and fungi were highest in Houhuo and Hongxin among the three types of LTD, respectively. The different production temperatures of LTD had little effect on its microbial variety, but obviously impacted the microbiota structure and metagenomic function of LTD. Although the microbiota of the three types of LTD shared a high commonality, each had specific microbiota and functional metagenomic features, suggesting their different but complementary roles in the LFB fermentation process. The representative dominant microbes in Houhuo were mostly involved in metabolic pathways associated with the production of flavor substances in liquor. In contrast, the enriched microbes in Qingcha and Hongxin were not only capable of producing specific flavor substances but also had a strong ability to degrade macromolecular substances in raw materials, promoting microbial growth. This study has greatly enriched our knowledge of the effect of LTD fermentation temperature on its quality, providing practical and interesting information for future improvement of LTD and light-flavor Baijiu products.